Croatia : Accounting and Auditing - World Bank (Washington, DC, 2013)
This report is based on an assisted self-assessment of accounting and auditing standards and practices in Croatia conducted under the management of a National Steering Committee consisting of representatives form government and the private sector. The self-assessment exercise, complemented by due diligence by Bank staff, specifically focused on the strengths and weaknesses of the institutional arrangements needed for the observance of International Accounting Standards (IAS) and International Standards of Auditing (ISA). The Accounting Act was amended in 1992 in order to adopt a more investor oriented approach. The Act took the important step of requiring all companies to prepare IAS financial statements. The Audit Law requires that the audit should be carried out by a certified auditor licensed under authority granted by the Ministry of Finance (MOF) and in accordance with ISA.